Science for social licence to arrest an ecosystem-transforming invasion - Norman W. H. Mason; Nicholas A. Kirk; Robbie J. Price; Richard Law; Richard Bowman; Rowan I. Sprague (Biological Invasions, 2023)

Integrating across knowledge systems to drive action on chronic biological invasions - Norman W. H. Mason; Olivia Burge; Robbie Price; Rowan Sprague; John Dymond; Mike Watt; Tessa Roberts; Thomas Paul; Brian Richardson; Carol Rolando; Sarah Wyse; Philip E. Hulme; et al. (Biological Invasions, 2021)

Saved from extinction? Establishment and dispersal of Mercury Islands tusked weta, Motuweta isolata, following translocation onto mammal-free islands - Ian Stringer; Corinne Watts; Danny Thornburrow; Rob Chappell; Robbie Price (Journal of Insect Conservation, 2014)

Secondary woody vegetation patterns in New Zealand's South Island dryland zone - Susan Walker; Nigel King; Adrian Monks; Sophie Williams; Larry Burrows; Ellen Cieraad; Colin Meurk; Jacob McC Overton; Robbie Price; Mark Smale (New Zealand Journal of Botany, 2009)
Can New Zealand's indigenous dryland ecosystems be rehabilitated by facilitating inherent successional tendencies to enhance development of indigenous‐dominated and often woody communities in the long term? Here, we describe the geographic distribution of woody communities of New Zealand's South Island drylands to generate hypotheses about successional trajectories to future vegetation states. Presences and absences of woody species in 3880 vegetation plots collated from past surveys were used to predict species potential distributions across drylands. Separate models and spatial predictions were built for each of four classes of woody richness, which were used as surrogates for successional stages. Woody species richness increased significantly from grassland to shrubland and from shrubland to forest cover, and trends in species traits also suggest richness class was related with successional stage. Indigenous woody species outnumbered exotic species in all richness classes. Assuming richness classes represent temporal progressions, our results suggest relatively homogeneous early‐successional woody associations succeed to a divergent array of woody associations in different environments. Growth forms of species in our predicted associations suggest transitions from grassland to tall, tree‐rich forests in northern and coastal drylands, and to liane‐rich open or lightcanopied shrubland, woodland, or low forest in more severe inland environments. These putative communities are novel in species composition but physiognomically broadly similar to pre‐settlement analogues. Especially in severe inland environments, unassisted transitions from grassland to indigenousdominated late‐successional woody communities may depend on the exclusion of tall exotic trees, Scotch broom, and gorse in early succession.

An Index of Risk as a Measure of Biodiversity Conservation Achieved through Land Reform - SUSAN WALKER; ROBBIE PRICE; R.T. THEO STEPHENS (Conservation Biology, 2008)
We measured the net progress of land reform in achieving a national policy goal for biodiversity conservation in the context of ongoing clearing of native vegetation and additions of land to a highly nonrepresentative (residual) reserve network, interior South Island, New Zealand. We used systematic conservation‐planning approaches to develop a spatially explicit index of risk of biodiversity loss (RBL). The index incorporated information from national data sets that describe New Zealand's remaining indigenous land cover, legal protection, and land environments and modeled risk to biodiversity on the basis of stated assumptions about the effects of past habitat loss and legal protection. The index identified irreplaceable and vulnerable native habitats in lowland environments as the most at risk of biodiversity loss, and risk was correlated with the density of threatened plant records. To measure achievement, we used changes in the index that reflected gains made and opportunity costs incurred by legal protection and privatization. Application of the index to measure the difference made by land reform showed it had caused a net increase in the risk of biodiversity loss because most land vulnerable to habitat modification and rich in threatened plant species was privatized and land at least risk of biodiversity loss was protected. The application revealed that new high‐elevation reserves did little to mitigate biodiversity decline, that privatization of low‐elevation land further jeopardized the most vulnerable biodiversity in lowland native habitats, and that outcomes of land reform for biodiversity deteriorated over time. Further development of robust achievement measures is needed to encourage more accountable biodiversity conservation decisions.

Land use effects on “spring annual” herbs in rare non‐forest ecosystems of New Zealand - Geoffrey Rogers; Jacob McC. Overton; Robbie Price (New Zealand Journal of Botany, 2007)
We examined trends over six consecutive spring seasons in three “spring annual” herbs, Myosurus minimus subsp. novae‐zelandiae (Ranunculaceae), Ceratocephalapungens (Ranunculaceae), and Myosotis pygmaea var. minutiflora (Boraginaceae), in terms of their habitats and site land uses in several rare, non‐forest ecosystems. On dry hillslopes, saline soils, and turfs of ephemeral wetlands (including coastal turfs), Ceratocephala and Myosotis declined where sites were managed for conservation by removal of mammalian herbivores. Some populations of Myosurus declined only marginally or remained stable despite high cover of ruderal and weedy, herbaceous exotic plants. Loss of monitored populations during the study was offset by discoveries of additional populations of all three taxa. Statistical models of population trends suggest that in some instances spring annual populations benefit from farm animal and rabbit ( Oryctolagus cuniculus cuniculus ) disturbance of their habitats perhaps by 1) suppressing transitions to taller vegetation and retarding competition of invasive exotic plants and 2) maintaining nutrient supplementation from faeces lost with the extinction of ground‐dwelling birds. Frequent seeds of all three taxa preserved in moa coprolites from several sites in Central Otago point to 1) the herbs’ probable non‐rarity in pre‐human times and 2) dispersal mutualisms and mediation of community ground cover by extinct ratites.